Hot water extract of Agaricus blazei Murrill specifically inhibits growth and induces apoptosis in human pancreatic cancer cells - Yoshihisa Matsushita; Yoshiyuki Furutani; Rumiko Matsuoka; Toru Furukawa (BMC, 2018)
Abstract Background Pancreatic cancer is one of the most aggressive human malignancies. The development of a novel drug to treat pancreatic cancer is imperative, and it is thought that complementary and alternative medicine (CAM) could yield such a candidate. Agaricus blazei Murrill is a CAM that has been tested as an anticancer drug, but its efficacy against pancreatic cancer is poorly understood. To study the potential of A. blazei in the treatment of pancreatic cancer, we examined the effects of its hot water extract on the proliferation and global gene expression profile of human pancreatic cancer cells. Methods Three distinct human pancreatic cancer cell lines, MIAPaCa-2, PCI-35, and PK-8, and the immortalized human pancreatic duct-epithelial cell line, HPDE, were employed. The cells were incubated with the appropriate growth medium supplemented with the hot water extract of A. blazei at final concentrations of 0.005, 0.015%, or 0.045%, and cellular proliferation was assessed for five consecutive days using an MTT assay. Apoptosis was examined by using flow cytometry and the terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay. Caspase-dependent apoptosis was assayed using immunoblotting. Global gene expression profiles were examined using a whole human genome 44 K microarray, and the microarray results were validated by using real-time reverse transcription PCR. Results The hot water extract of A. blazei significantly inhibited the proliferation of cultured pancreatic cancer cells through the induction of G0/G1 cell cycle arrest and caspase-dependent apoptosis; the effect was the smallest in HPDE cells. Furthermore, significant alterations in the global gene expression profiles of pancreatic cancer cells occurred following treatment with the hot water extract of A. blazei. Genes associated with kinetochore function, spindle formation, and centromere maintenance were particularly affected, as well as cyclins and cyclin-dependent kinases that are essential for cell cycle progression. In addition, proapoptotic genes were upregulated. Conclusions The hot water extract of A. blazei may be useful for the treatment of pancreatic cancer and is a potential candidate for the isolation of novel, active compounds specific for mitotic spindle dysfunction.